Journal of Oceanography - Journal of Oceanography (Springer Nature, 2026)
The Journal of Oceanography is the official journal of the Oceanographic Society of Japan and open to all oceanographers in the world. The main aim of the journal is to promote understandings of ocean systems from various aspects including physical, chemical, biological, geological oceanography as well as paleoceanography, etc.
FI 0.55
Q4
Keywords: Earth; Space & Environmental Sciences; Oceanography & Paleoceanography; Oceanografía; Paleoceanografía; Acuerdos transformativos; Transformative agreements; Pacífico norte occidental; Aguas costeras asiáticas